2019
DOI: 10.3906/bot-1812-36
|View full text |Cite
|
Sign up to set email alerts
|

Biology of flowering and insect visitors of Iris aphylla L. (Iridaceae)

Abstract: The marginal character of the I. aphylla populations, their spatial isolation, and the isolated 'island' localities (valley slopes, mineral islands surrounded by a peat bog) determine the varying characteristics of these populations (Franszczak-Być and Dąbrowska, 1993;Czarnecka, 1994;Wróblewska, 2003). Marginal populations naturally tend to become rare and endangered. They are usually described as populations with persistent low abundance, poor flowering, sparse fruiting, evident dominance of vegetative reprod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The attractive and fragrant I. aphylla flowers are the only source of nutrients and a mating site for the beetle, which is unable to damage the seeds. The observations showed that I. aphylla was the first to start flowering, i.e., in the first half of May [ 34 ]. In turn, I. sibirica flowered in the second half of the month.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The attractive and fragrant I. aphylla flowers are the only source of nutrients and a mating site for the beetle, which is unable to damage the seeds. The observations showed that I. aphylla was the first to start flowering, i.e., in the first half of May [ 34 ]. In turn, I. sibirica flowered in the second half of the month.…”
Section: Resultsmentioning
confidence: 99%
“…The following parameters of the species were assessed in the experiment: The observations showed that I. aphylla was the first to start flowering, i.e., in the first half of May [34]. In turn, I. sibirica flowered in the second half of the month.…”
Section: Characteristics Of Seed Capsules and Seedsmentioning
confidence: 99%
“…In 2003, there were only 8 populations in natural sites in Poland, 4 of which were reintroduced [38]. The most recent reports state that there are 10 such sites, mainly located in the Małopolska Upland, Lublin Upland and Biebrza National Park [39]. Natural succession, consisting of heavy overgrowth by trees and shrubs, is cited as the cause of its habitat destruction [38].…”
Section: Galanthus Leucojum Gladiolus and Irismentioning
confidence: 99%
“…Positiv zu erwähnen ist die Tatsache, dass viele durchschnittlich erfasste Merkmalswerte (z. B. für Wuchshöhe, Länge der Blätter, Anzahl und Länge der Blüten) von I. aphylla mit denen in der Literatur(Cassidy & Linnegar 1987, Bricknell 1994, Dykes 2015, Jäger 2017, Dąbrowska et al 2019) übereinstimmten, sodass das Wachstum und die Fitness der Individuen als optimal angesehen werden können.Iris aphylla ist ein Rhizom-Hemikryptophyt(Jäger 2017), sodass sich die Art einerseits vegetativ reproduzieren und andererseits Nährstoffe effizient speichern kann, was mit einer hohen Lebensdauer und einer damit verbundenen standörtlichen Treue einhergehen könnte. Hinzu kommt, dass im ‚Rothmaler' bei I. aphylla die Zeigerwertzahlen für Feuchtigkeit (3), Reaktion…”
unclassified